If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -4) = 2x + 5(x + -2) Reorder the terms: 5(-4 + x) = 2x + 5(x + -2) (-4 * 5 + x * 5) = 2x + 5(x + -2) (-20 + 5x) = 2x + 5(x + -2) Reorder the terms: -20 + 5x = 2x + 5(-2 + x) -20 + 5x = 2x + (-2 * 5 + x * 5) -20 + 5x = 2x + (-10 + 5x) Reorder the terms: -20 + 5x = -10 + 2x + 5x Combine like terms: 2x + 5x = 7x -20 + 5x = -10 + 7x Solving -20 + 5x = -10 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -20 + 5x + -7x = -10 + 7x + -7x Combine like terms: 5x + -7x = -2x -20 + -2x = -10 + 7x + -7x Combine like terms: 7x + -7x = 0 -20 + -2x = -10 + 0 -20 + -2x = -10 Add '20' to each side of the equation. -20 + 20 + -2x = -10 + 20 Combine like terms: -20 + 20 = 0 0 + -2x = -10 + 20 -2x = -10 + 20 Combine like terms: -10 + 20 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| x*.44=110 | | 8x=90+2x | | 16(3x)=64(x+5) | | h(x)=(2x-6) | | 28-0.3=0.74-12 | | 9(w-6)= | | 8w^2-2122w+20000=0 | | 2d+4=10+6d | | 11-7*2+3= | | x*.16=4 | | (x^3)+(5x^2)-x-5=0 | | 8/7y-4/7 | | 8x+10=6x-12 | | x*.15=3 | | 4c=2c+9 | | 7.37x+64=54.3169+8x | | 6/7x-3/7=9 | | 6.95x+34.75=69.5 | | 99-w=208 | | 8.6a+11=114.2 | | 21=8d-9(2d+1) | | x^2+14x-106=0 | | 10/11x-2/11=5 | | 9x(7-4)*2+9= | | 22.5=6.3w+1.2w | | -3*1/6y-18=72 | | 4x-2+1=15 | | 2z=z-3 | | 110+58=y | | 1-3(n+5)=-4 | | -10=5w+5 | | z-3=9z+53 |